The future of work in automated warehouse from the perspective of the employees - Bałys, Paulina; Buła, Piotr; Dziedzic, Dorota; Uznańska, Marta (Contemporary organisation and management. Challenges and trends, 2020)
Contemporary enterprises operate in conditions of high uncertainty, where competition takes place not only at the level of prices of products or services offered, but above all on quality. The time taken to deliver a product or service is one of the most important quality measures. The role and importance of the logistics system in the current competitive environment is of fundamental importance. Warehouses have ceased to be perceived as cost centers, just being a central place in the flow of goods, and are gaining ever more importance in building a lasting competitive advantage. There are also growing requirements for modern warehouses (identification of the place where the goods are stored, efficient means of internal transport, the possibility of quick product picking). Technological progress and automation has a huge impact on the way warehouse processes are carried out and managed. And this technology is developing extremely quickly, radically changing work in the warehouse. Elimination of errors, increased efficiency, significant reduction of operating costs, assurance of constant availability of the full range of goods, the improvement of process control, increase of precision and speed of information flow are some of the benefits of introducing automation in the warehouse. Although warehouse processes are becoming increasingly automated, people will still have to a role by collaborating and interacting with machines. Due to the fact that the interaction between man and machine in warehouse work has not been the subject of much attention in contemporary literature on the subject, the purpose of the article is to assess the impact of automation on warehouse work, through CAPI research directed at warehouse employees. What impact the current technology has on people’s work was assessed, whether large fluctuations and staff shortages among warehouse workers are not a repercussion of treating them as supplementary to modern machines, or whether they feel at risk of losing their jobs due to automation.